Modern Business Organisations and Bluetooth Advertising - Singh, Gurmeet; Gautam, Harish (Indian Journal of Marketing, 2004)
Every business is a social institution. Quite often, it is called a child of environment. Business is an open system, influencing environment and being influenced by environment. As it is expected to deliver goods or services in the light of on-going changes both at micro and macro levels, it has to be efficient in its onerous task of communicating with its customers widely spread all around the world. For mass communication of the companies with widely spread customers, the Advertising is the only way out. The real challenge before such companies is regarding the selection of the most suitable Advertising Media Mix. An Advertising medium is a means or vehicle of delivering a definite message to its target customer. Advertising media mix involves selection of the most cost-effective media to deliver the desired number of exposures to the target audience.